The king's commissioners - Friedman, Aileen; Guevara, Susan (New York : Scholastic, 1994)
While trying to keep track of his many royal commissioners, the king learns some new ways of counting.
"A Marilyn Burns brainy day book."
Keywords: Counting -- Fiction; Mathematics -- Fiction; Kings, queens, rulers, etc. -- Fiction